Eksplorasi dan Penentuan Ras Penyebab Penyakit Blas Padi di Kabupaten Maros - Nur Azizah Salimah; Tutik Kuswinanti; Andi Nasruddin (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2021)
Exploration and Determination of Rice Blast Races in Maros Regency Blast disease caused by the fungus Pyricularia oryzae (Teleomorph: Magnaporthe oryzae) is one of the most important diseases causing significant yield losses on rice worldwide. The fungus has a high degree of virulence and adaptation as evidenced by the large number of its races. The study was conducted to identify the race of P. oryzae isolates and their distribution in eight sub-districts in Maros Regency. Race identification was determined based on bioassay using seven differential rice varieties, i.e. Asahan, Cisokan, IR 64, Krueng Aceh, Cisadane, Cisanggarung and Kencana Bali varieties. Observation of disease severity followed the Standard Evaluation System for Rice by IRRI. Susceptibility of host plant was assessed based on leaf spot symptom on the scale of 5 to 9. As many as 30 isolates of P. oryzae were found with the distribution as follows, 4 isolates from Bantimurung, 8 isolates from Simbang, 4 isolates from Maros Baru, 3 isolates each from Moncongloe, Tanralili, Tompobulu, Mandai, and 2 isolates from Lau. A total of 17 P. oryzae races were identified, namely race 000, 001, 011, 020, 023, 031, 033, 041, 061, 101, 103, 111, 141, 173, 221, 301 and 373. Race 001 is the dominant race in which it was found at five locations where P. oryzae isolates were collected.